Fabrication and Characterization of Electrospun Silver Nanofibers with Unmatched Porosity - Jahir Hussain, Fathima Shahitha; M. M., Yusoff (2012)
Herein we describe the fabrication and characterization of free standing silver nanofibers with very high porosity using electrospun polymer nanofibers as template. Silver (Ag) metal was deposited on these porous nanofibers using thermal evaporator. The polymer nanofibers (template) and silver nanofibers were characterized using scanning electron microscopy, XRD and cyclic voltammetry. The Ag nanofibers showed high electrical conductivity.